Livestock production and the water challenge of future food supply: Implications of agricultural management and dietary choices. (November 2017) - Weindl, Isabelle; Bodirsky, Benjamin Leon; Rolinski, Susanne; Biewald, Anne; Lotze-Campen, Hermann; Müller, Christoph; Dietrich, Jan Philipp; Humpenöder, Florian; Stevanović, Miodrag; Schaphoff, Sibyll; Popp, Alexander
Highlights: Impacts of diets and livestock productivity on global water resources are quantified. Dietary changes reduce agricultural water consumption, but mainly of green origin. Secondary effects lower the potential of dietary changes to abate blue water use. Dietary changes and livestock management can only slow down expansion of irrigation. Abstract: Human activities use more than half of accessible freshwater, above all for agriculture. Most approaches for reconciling water conservation with feeding a growing population focus on the cropping sector. However, livestock production is pivotal to agricultural resource use, due to its low resource-use efficiency upstream in the food supply chain. Using a global modelling approach, we quantify the current and future contribution of livestock production, under different demand- and supply-side scenarios, to the consumption of "green" precipitation water infiltrated into the soil and "blue" freshwater withdrawn from rivers, lakes and reservoirs. Currently, cropland feed production accounts for 38% of crop water consumption and grazing involves 29% of total agricultural water consumption (9990 km 3 yr −1 ). Our analysis shows that changes in diets and livestock productivity have substantial implications for future consumption of agricultural blue water (19–36% increase compared to current levels) and green water (26–69% increase), but they can, at best, slow down trends of rising water requirements for decades to come. However, moderate productivity reductions in highly intensive livestock systems are possible without aggravating water scarcity. Productivity gains in developing regions decrease total agricultural water consumption, but lead to expansion of irrigated agriculture, due to the shift from grassland/green water to cropland/blue water resources. While the magnitude of the livestock water footprint gives cause for concern, neither dietary choices nor changes in livestock productivity will solve the water challenge of future food supply, unless accompanied by dedicated water protection policies.